Voltage Induced Effect for Vibration Suppression Using Eddy Current on Power Steering System - Mohamad Zairi, Baharom; Priyandoko, Gigih; F. R. M., Romlay; M. S. M., Sani; M. S., Salleh; M. H. M., Yusof (Asian Research Publishing Network (ARPN), 2015)
This paper describes the study of vibration suppression by using eddy current as a suppression agent on a power steering system. Vibration occurs due to some factors such as engine vibration, road surfaces, vibration direction, tire characteristics, suspension design and steering devices. The objective of this study is to investigate the voltage induced effect on vibration suppression occurred at power steering system using eddy current braking. Equipments involve are accelerometer, data acquisition (DAQ), electric motor, transformer, aluminium disc and Voltage regulator. Position of the accelerometer was placed at the steering wheel and aluminium disc. Based on the result for frequency domain, in a normal condition, the level of vibration amplitude produce is 0.2348mvolt. while, after voltage was apply to power steering system lowest vibration suppression at steering column (aluminium disc) is 0.166mvolt with 2mm air gap opening using 48 volt power supply. For steering wheel, in a normal condition is the level of vibration is 0.2251mVolt. After voltage was applied to power steering system, the lowest vibration suppression at steering wheel is 0.1836mVolt using 96 Volt of voltage induced. Based on the experimental result, increasing voltage induced managed to reduce vibration on power steering system since the electromagnetic braking force using eddy current increase which act as the vibration suppression agent.